The Benefits of Using Social Media in the Learning Process of Students in the Digital Literacy Era and the Education 4.0 Era - AGUS PURWANTO; Khaerul Fahmi; Yoyok Cahyono (Journal of Information Systems and Management (JISMA), 2023)
The aim of this work is to investigate the potential benefits of using social media in education. The results of the analysis reveal that social media has many advantages in the learning process of students. The purpose of this paper is to explore the benefits of social media in education. Thorough examination has actually revealed that this online social media tool has many educational benefits. Indeed, it has been shown that social media enhances communication and interaction between students and between teachers and students. Thanks to this platform, teachers and students can now communicate with each other within or between classes. Social media is an effective way to promote student engagement to share ideas and to express their opinions in a more comfortable way. The advantage of social media applications is that they foster collaboration; given that they offer teachers and students a destination where they can bring their ideas together, social media can be used as a valuable educational tool capable of enriching the learning experience. Therefore, we recommend that educators use these online social communities whether learning is fully online, blended, or face-to-face.